The Correlation of PPARα Activity and Cardiomyocyte Metabolism and Structure in Idiopathic Dilated Cardiomyopathy during Heart Failure Progression - E. Czarnowska; D. Domal-Kwiatkowska; E. Reichman-Warmusz; J. B. Bierla; A. Sowinska; A. Ratajska; K. Goral-Radziszewska; R. Wojnicz (PPAR Research)
This study aimed to define relationship between PPARα expression and metabolic-structural characteristics during HF progression in hearts with DCM phenotype. Tissue endomyocardial biopsy samples divided into three groups according to LVEF ((I) 45–50%, n=10; (II) 30–40%, n=15; (III) <30%, n=15; and control (donor hearts, >60%, n=6)) were investigated. The PPARα mRNA expression in the failing hearts was low in Group (I), high in Group (II), and comparable to that of the control in Group (III). There were analogous changes in the expression of FAT/CD36 and CPT-1 mRNA in contrast to continuous overexpression of GLUT-4 mRNA and significant increase of PDK-4 mRNA in Group (II). In addition, significant structural changes of cardiomyocytes with glycogen accumulation were accompanied by increased expression of PPARα. For the entire study population with HF levels of FAT/CD36 mRNA showed a strong tendency of negative correlation with LVEF. In conclusion, PPARα elevated levels may be a direct cause of adverse remodeling, both metabolic and structural. Thus, there is limited time window for therapy modulating cardiac metabolism and protecting cardiomyocyte structure in failing heart.